2016
DOI: 10.1007/s40865-016-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Developmental Trajectories Of Girls’ Offending And Police Charges: Results From The Pittsburgh Girls Study

Abstract: The current study is based on longitudinal self-reported data from the Pittsburgh Girls Study (N = 2,450). This is the largest follow-up delinquency study of girls in the USA; an inner-city population of girls, between the ages of 11 and 18. We first investigated self-reported developmental trajectories for delinquency, and we then examined the correspondence between these selfreported delinquency trajectories and later police charges. The results show three self-reported delinquency trajectories for the PGS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
8
0
7
Order By: Relevance
“…This model provides for the statistical identification of subgroups of individuals while also allowing the researcher to estimate the effect of both time-invariant and time-variant predictors of behavior (Nagin, 2005). Consistent with prior research on crime and delinquency using trajectory models (Ahonen et al, 2016) and the skewness of the outcome variable, we estimated a zero-inflated Poisson trajectory form. Following the identification of the most accurate number of groups, we estimated models with various parametric identifications that arrive at the overall best-fitting models as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model provides for the statistical identification of subgroups of individuals while also allowing the researcher to estimate the effect of both time-invariant and time-variant predictors of behavior (Nagin, 2005). Consistent with prior research on crime and delinquency using trajectory models (Ahonen et al, 2016) and the skewness of the outcome variable, we estimated a zero-inflated Poisson trajectory form. Following the identification of the most accurate number of groups, we estimated models with various parametric identifications that arrive at the overall best-fitting models as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Females who were in the “high rate” and “low rate” group were significantly more likely to experience an officially recorded police charge compared with those in the non-offender group. Their results also indicated that the high-rate offending females were more versatile in their offenses than those offending at lower rates (Ahonen et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, investigations of community samples of women also identified limited heterogeneity. Three trajectories were typically identified that were defined by nonoffending, low-rate offending, and high-rate offending (Ahonen et al, 2016; Cohen et al, 2010; D’Unger et al, 2002; Jennings et al, 2018; Loeber et al, 2017). In these studies, the nonoffending trajectory was most prevalent, ranging from 72.5% (Loeber et al, 2017) to 89.9% (Cohen et al, 2010).…”
Section: Patterns Of Offendingmentioning
confidence: 99%
“…Cohen et al (2010) suggested that female offending patterns amounted to either offending or nonoffending, which aligned with Moffitt and Caspi’s (2001) perspective. The lack of heterogeneity identified within community-based studies may relate to a tendency to only follow participants until mid to late adolescence (e.g., Ahonen et al, 2016; Jennings et al, 2018; Lahey et al, 2006; Loeber et al, 2017). A longer follow-up period may be needed given that Moffitt (1993) asserted that AL and LCP offending patterns would resemble each other during adolescence.…”
Section: Patterns Of Offendingmentioning
confidence: 99%